2000
DOI: 10.1034/j.1600-0609.2000.90087.x
|View full text |Cite
|
Sign up to set email alerts
|

β‐Thalassaemia intermedia in Lebanon

Abstract: Approximately one third of thalassaemia patients on record in Lebanon have thalassaemia intermedia. We have analysed three factors in a panel of 73 patients with this less severe form of the disease in our population: mild beta-globin gene mutations, deletions in the alpha-globin gene and the presence of a polymorphism for the enzyme Xmn I in the Ggamma-promoter region. The results show that the most important contributing factor is the beta-genotype: 68% of patients have a mild beta+ mutation (IVSI-6, cd29, -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 9 publications
5
13
2
1
Order By: Relevance
“…This is to a considerable extent comparable with studies from some Mediterranean countries like Lebanon and Italy, where the inheritance of mild β + alleles is responsible for the majority of their TI cases [7, 15]. Another frequently encountered contributor was Xmn I polymorphism which was seen in 19/20 families (95%) with β ο / β ο and in 9/13 (69.2%) with β ο / β + but in none (0%) of those with β + / β + or those with β ο /wild genotypes (Table 2).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This is to a considerable extent comparable with studies from some Mediterranean countries like Lebanon and Italy, where the inheritance of mild β + alleles is responsible for the majority of their TI cases [7, 15]. Another frequently encountered contributor was Xmn I polymorphism which was seen in 19/20 families (95%) with β ο / β ο and in 9/13 (69.2%) with β ο / β + but in none (0%) of those with β + / β + or those with β ο /wild genotypes (Table 2).…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with the findings of Verma and coworkers (2007) who demonstrated a similar pattern among 325 TI patients from different ethnic backgrounds in the Mediterranean region and Asia and concluded that this polymorphism is the commonest ameliorating factor in cases with β 0 mutations but not β + [16]. Accordingly in neighboring Iran, where β 0 mutations are more frequent than β + in TI patients, Xmn I polymorphism was reported as the most frequent ameliorating factor [17], while the latter polymorphism comes second in importance in the Lebanese and the Italians [7, 15], and it is almost irrelevant among Cypriots TI where β + mutations predominate [16]. The Xmn I polymorphism is one of three major Hb F quantitative trait loci (QTLs) responsible for Hb F variation, and it leads to a less severe phenotype by increasing γ chain production, which helps to neutralize unbound α -chains [18, 19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlation was carried out between the XmnI [+] category and the six common mutations individually, which showed that 68% of chromosomes in the XmnI [+] category had the FSC 8 (−AA) mutation ( Table 2). The results reported here show that there is a positive correlation between the FSC 8 mutation and the −158 (C→T) polymorphism of the G γ-globin gene (p <10 −5 ) which had been previously reported in different populations (18,19).…”
Section: Xmni G G Polymorphismsupporting
confidence: 55%
“…Co-inheritance of two single α-globin gene deletions (-α 3.7 or -α 4.2 deletion) in β-thalassaemia major can result in a clinical phenotype of β-thalassaemia intermedia [35]. A study on β-thalassaemia intermedia patients in Lebanon showed regular blood transfusion treatments, which can result in adverse effects, were avoided with early diagnosis of thalassaemia intermedia [36]. This is paramount to avoid treatment with regular blood transfusions as this can have adverse clinical effects.…”
Section: Discussionmentioning
confidence: 99%